2000
DOI: 10.1007/s004240000487
|View full text |Cite
|
Sign up to set email alerts
|

Within-subject electrocardiographic differences at equal heart rates: role of the autonomic nervous system

Abstract: Various combinations of sympathetic and vagal tone can yield the same heart rate, while ventricular electrophysiology differs. To demonstrate this in humans, we studied healthy volunteers in the sitting position with horizontal legs. First, heart rate was increased by lowering the legs to 60 degrees and back. Thereafter, heart rate was increased by handgrip. In each subject, a leg-lowering angle was selected at which heart rate matched best with heart rate in the third handgrip minute. Thirteen subjects had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 38 publications
(47 reference statements)
0
28
0
Order By: Relevance
“…Although the clinical applicability of these concepts remains to be fully validated, significant progress toward validation of the T peak-T end interval as an index of TDR has been achieved. Recent studies suggest that the T peak-T end interval may be a useful index of transmural dispersion and thus may be prognostic of arrhythmic risk under a variety of conditions (13)(14)(15)(16)(17)(18)(19)(20). Direct evidence in support of T peak-T end as a valuable index to predict TdP in patients with long QT syndrome was provided by Yamaguchi et al (21).…”
Section: Role Of Electrical Heterogeneity In the Inscription Of The Tmentioning
confidence: 96%
“…Although the clinical applicability of these concepts remains to be fully validated, significant progress toward validation of the T peak-T end interval as an index of TDR has been achieved. Recent studies suggest that the T peak-T end interval may be a useful index of transmural dispersion and thus may be prognostic of arrhythmic risk under a variety of conditions (13)(14)(15)(16)(17)(18)(19)(20). Direct evidence in support of T peak-T end as a valuable index to predict TdP in patients with long QT syndrome was provided by Yamaguchi et al (21).…”
Section: Role Of Electrical Heterogeneity In the Inscription Of The Tmentioning
confidence: 96%
“…The T peak -T end interval is unlikely to provide an absolute measure of transmural dispersion in vivo, as elegantly demonstrated by Xia and co-workers (151). However, changes in this parameter are thought to be capable of reflecting changes in spatial dispersion of repolarization, particularly TDR, and, thus, may be prognostic of arrhythmic risk under a variety of conditions (57,102,125,126,144,150). Takenaka et al (125) recently demonstrated exercise-induced accentuation of the T peak -T end interval in LQT1, but not LQT2, patients.…”
Section: Long Qt Syndromementioning
confidence: 99%
“…4 On the contrary, if the QT/RR hysteresis is ignored, QTc correction can be polluted by substantial errors if data are taken from episodes during which the heart rate is changing, with potentially disputable conclusions. 26 At the same time, although QT/RR hysteresis correction reduces QTc variability and thus improves the power of studies of drug-induced QTc changes, 4 QT/RR hysteresis correction is not crucial (in the sense that it could lead to false positive or false negative conclusions) if QT readings are obtained only from episodes preceded by stable heart rates. In the studies of drug effects, this is unachievable only with very fast acting pharmaceuticals.…”
Section: Discussionmentioning
confidence: 99%